Legal Reform Related to Interracial Koreans - Sungjin Yoo (Washington University Global Studies Law Review, 2017)
Since the 1997 financial crisis, South Korea has strived to compete on the world economic stage and has now emerged as Asia’s fourth-largest economy as well as a major player among the world’s top developed nations. Through private companies’ cross-border transactions and the South Korean government’s signing of free trade agreements with other countries, South Korea continues to globalize economically and grow as an international business hub. Yes, extensive globalization has not weakened South Korea’s nationalistic mindset. According to recent polls by the Ministry of Gender Equality and Family and the Asian Institute, nearly eighty-seven percent of South Koreans stress the importance of Korean blood lineage while thirty-two percent of Koreans consider mixed-race families as a “threat to social cohesion.” Eighty-three percent of South Koreans also believe Korean descendants living abroad still belong to the Korean ethnicity even if they have become residents or citizens of a foreign country. Ethnic homogeneity based on blood and ancestry continues to play a key role in South Korean society. This ethnic nationalism, though crucial to cultural preservation during Japanese colonial rule, has had oppressive, discriminatory effects on those who do not fit the mold. Part II of this note will examine the background on Korea’s ethnic nationalism. Part III will discuss Korea’s historical and post-Korean War experience with non-Koreans. In Part IV, the treatment of two significant groups of interracial Koreans, the Amerasians and Koasians, will be examined. Part V will consider the current laws and legal reform regarding the better treatment of interracial Koreans.
Keywords: South Korea; ethnic nationalism; Amerasians; Koasians; ethnic homomgeneity; mixed-race; blood lineage; xenophobia; pan-asianism; anti-discrimination; CERD